Model Evaluasi Penerimaan Pengguna Sistem Informasi Rekam Medis di Sektor Kesehatan - Ni Kadek Armini; Aris Puji Widodo; Suhartono Suhartono (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2017)
In the development of advanced technology, information users are required to follow the progress that has grown rapidly. One of the programs implemented by the Ministry of Health of the Republic of Indonesia has issued a policy that guides the implementation of health development implemented by the government and private sector in order to improve the quality of information in this case the quality of medical record information. And one of the efforts to improve the quality of medical record information in the hospital in the form of the application of Medical Record Information System (SIRM). Application of SIRM is currently experiencing obstacles and barriers in the level of user acceptance. There are still many things that are operational and managerial, making the implementation of SIRM is not going well. . This study evaluates the results of SIRM implementation to process the data of inpatients at Undata Hospital of Central Sulawesi Province from the user acceptance level, using the combined model of Unified Theory of Acceptance and Usage of Technology (UTAUT) and Human, Organization, Technology Fit (HOT Fit ).